Impact of Postharvest Operations on Rice Grain Quality: A Review. Issue 3 (18th March 2019) - Tong, Chuan; Gao, Haiyan; Luo, Shunjing; Liu, Lei; Bao, Jinsong
Abstract: Postharvest operations, such as drying, storage, and milling, have been used to ameliorate the aging of rice grains and to achieve and maintain desirable rice grain quality, and thus play a key role in determining rice commercial quality and value. This review summarizes publications from the past decade and outlines the evidence supporting attribution of grain quality changes induced by postharvest processes to changes in the physical properties and chemical composition of the rice grain (starch, protein, lipids, and antioxidants). Rice drying mainly affects rice milling quality as rice kernel fissuring that may occur during drying leads to head rice yield reduction. Rice grain aging occurring during storage is inevitable and responsible for the changes in rice appearance, milling, eating, cooking, and nutritional quality. As milling significantly changes the chemical composition of rice by removing protein‐ and lipid‐rich bran layers, milling can alter the aging process of rice and also affect rice appearance, eating, and sensory quality, but mainly affects the nutritional quality. Therefore, drying methods, storage conditions, and milling methods warrant further research to achieve and maintain the desired rice grain quality. This review may contribute to better understanding of the impacts of postharvest processes on rice grain quality, and provide insights into potential improvements in these practices for rice production and utilization in the whole rice industry.